An Investigation of the Long and Short Term Behavioral Effects of General Anesthesia on Pediatric Dental Patients With Autism - Tran, Janine; Chen, Jung-Wei; Trapp, Larry; McCormack, Laura (Frontiers in Oral Health, 2021)
Purpose: The purpose of this study was to compare the incidence of short and long term adverse behavioral effects of general anesthesia (GA) in healthy versus moderate to severe autistic (ASD) children. Methods: 40 healthy and 37 ASD children, aged 3 to 17 years, undergoing GA for dental surgery participated in this study. Their anesthesia records were reviewed, and their parents answered telephone surveys to assess activity level, sleep disturbances, gastrointestinal disturbances, central nervous system effects, and respiratory depression. Three follow-up surveys were taken 8 hours, 24 hours, and 3 months post-surgery. Results: 455 incidences of adverse behavioral effects occurred within 8 hours post-surgery. Significantly more ASD patients had difficulty walking (P=0.016) and nausea (P=0.030), while more healthy children snored in the car ride home (P=0.036) and talked about the dental surgery (P=0.027). Three months post-discharge, 6 ASD patients acted in a way that concerned caregivers compared to 0 healthy patients, (P=0.008). Incidence of adverse behavioral effects significantly decreased from 8 hours to 24 hours overall. Conclusions: Most behavioral effects occur within 8 hours post-surgery. There are potential long term adverse behavioral effects in ASD children from GA, but the chance is low and generally not long lasting.